2021
DOI: 10.3389/fphar.2021.669782
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Attenuates the Myocardial Injury Caused by Adriamycin by Inhibiting Autophagy

Abstract: Astragaloside IV (ASIV) is the main active component of Astragalus, and can ameliorate cardiomyocyte hypertrophy, apoptosis and fibrosis. In this experiment, we studied how ASIV reduces the cardiotoxicity caused by adriamycin and protects the heart. To this end, rats were randomly divided into the control, ADR, ADR + ASIV and ASIV groups (n = 6). Echocardiography was used to observe cardiac function, HE staining was used to observe myocardial injury, TUNEL staining was used to observe myocardial cell apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Such as, AS-IV improves renal fibrosis through modulating the SIRT1-NF-κB pathway along with autophagy activation [43]. AS-IV ameliorates cardiomyocyte apoptosis and fibrosis regulating autophagy [44]. In our study, we proved that ASV-IV induced autophagy in IPF through TEM and detection of autophagy-related genes, which was in line with previous study [45].…”
Section: Discussionsupporting
confidence: 90%
“…Such as, AS-IV improves renal fibrosis through modulating the SIRT1-NF-κB pathway along with autophagy activation [43]. AS-IV ameliorates cardiomyocyte apoptosis and fibrosis regulating autophagy [44]. In our study, we proved that ASV-IV induced autophagy in IPF through TEM and detection of autophagy-related genes, which was in line with previous study [45].…”
Section: Discussionsupporting
confidence: 90%
“…Astragaloside IV (AS-IV) is a main active ingredient extracted from Huangqi, a traditional edible and medicinal herb that has been used for over 2000 years ( Ren et al., 2013 ). Previous evidence suggested that Astragaloside IV exerts diverse biological activities, such as anti-oxidation ( Luo et al., 2021 ), suppressing inflammation ( Wan et al., 2018 ), modulating gut microbiota and gut-derived metabolites ( He Q. et al, 2020 ; Gong et al., 2021 ). AS-IV has also shown notable pharmacological effects on anti-myocardial fibrosis ( Lin et al., 2019 ; Wei et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we also observed SU-induced autophagy of H9c2 cell lines by using a transmission electron microscopy detection, which was suppressed by ASIV (data not shown). It has been reported that ASIV could attenuate the myocardial injury caused by adriamycin or lipopolysaccharide by inhibiting autophagy [ [37] , [38] , [39] ]. However, it remains elusive the role of autophagy in the antiapoptotic or cardioprotective effect of ASIV on SU-associated cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%